The Impact of New Subway Construction on the Commuting Methods and Time Utilization of Residents Along the Line: A Comparison Before and After the Completion of the Subway in Kunming City - Kun Zhao; Baohong He (ISPRS International Journal of Geo-Information)
Subway construction changes land use patterns, disrupting the balance between traffic supply and demand and influencing residents’ activity and travel behaviors along the route. Previous studies have often overlooked the multiple attributes of the subway and their varying impacts on daily activities. To understand how subway construction affects travel and activity patterns, this study analyzed travel data from two years before and after the opening of the Kunming Subway. Propensity score matching was used to control for socioeconomic changes unrelated to the subway. The findings show the following: (1) The subway’s introduction leads to the development of commercial and civic amenities around its stations, attracting wealthier and more educated residents, which contributes to gentrification. (2) Overall, subway construction extends urban residential and employment areas, increasing residents’ dependence on cars and promoting a more motor-centric lifestyle. As a result, the subway’s ability to reduce car usage is limited. (3) The subway alters the impact of the built environment on travel behavior, with residents closer to the subway experiencing shorter travel distances and reduced activity spaces, while those further away maintain longer travel distances and greater activity areas.